Estimaç\~ao das tabelas auxiliares de impostos e margens da matriz de insumo-produto com mínima perda de informaç\~ao: Algoritmo RAWS - Thiago Sevilhano Martinez (Instituto de Pesquisa Econômica Aplicada (IPEA), 2014)
– This paper develops the RAWS algorithm to estimate auxiliary tables of indirect taxes and margins related to the Brazilian input-output tables (IOTs) for 2000 and 2005. We derive RAWS by an information loss minimization problem, which explores the data structure from both the IOTs and supply and use tables (SUT) released by IBGE. We make use of recent advances in the international literature of matrix balancing methods, as the generalization of RAS for tables with negative cells. Finally, we also adjust the official IOTs for 2000 and 2005 to make them compatible to the 2005/2009 revision of the SUTs.
Keywords: D57; C67; E01; 330; input-output; National Accounts; RAS; matrix balancing